Effectiveness of Japan’s oda utilization in Vietnam = Hiệu quả sử dụng nguồn vốn ODA của Nhật Bản tại Việt Nam - Phạm, Thu Phương (2021)
This graduation paper is attempt to provide a broad look on Japan’s ODA in Vietnam since 1992 via evaluating the effectiveness of ODA utilization. This study involves the summary of existing researches such as research reports, newspapers and government statistics on Japan’s ODA in Vietnam. By assessing five criteria: relevance, effectiveness, impact, efficiency and sustainability, this research reveals that although ODA projects were highly relevant to development plans and needs of Vietnam as well as Japan’s ODA policy, effectiveness, impact, efficiency and sustainability in some projects were not highly appreciated due to the inadequacies of law system, the lack of the management skill and the shortage of technology and human resources. Moreover, some projects made mistakes about the plan-making and document preparation, so when there were some unexpected changes, Vietnam landed in the embarrassing situation. Drawing from these findings, the researcher gives some suggestions to improve the effectiveness of ODA utilization in Vietnam.